Reading Biographies for Developing Narrative Self - Shyangtan, Sharmila (Journal of Education and Research, 2019)
Biography is an important aspect of researching in education once one is planning for a narrative inquiry. Reading biography inspires me to think narratively. I am much interested in knowing and understanding the biography of the Dalai Lama not because of any religious footprints but because of his spiritual endeavours, which go beyond the humanist tradition of thinking. I have not canvassed any social research which questioned life before and after death. I do not have much interest in researching faith-based experience and the mystical experience of such a spiritual leader. I read a book from the sense of developing insights as a narrative inquirer.